Carrying capacity analysis in Bunaken National Park to support marine tourism activity (dive and snorkelling tourism). Issue 1 (May 2021) - Farhum, Mini Farida; Jompa, Jamaluddin; Restu, Muhammad; Salman, Darmawan
Abstract: The carrying capacity of an area for tourism is the number of tourists that can be physically present/undertaking certain activities in the area at a given time without significant disturbance to nature and other humans. This study estimated the potential environmental carrying capacity of Bunaken National Park for marine tourism, specifically for snorkelling and diving activities. This research was conducted from October 2019 to March 2020 in Bunaken National Park. The results showed a concentration of diving and snorkelling in the National Park around Bunaken Island (50% of all tourists) with other islands receiving 10% to 25% of tourist volume. This level could have a negative impact on the sustainability of the coral reef ecosystems around Bunaken Island; therefore, diving and snorkelling activities around this island need to be managed appropriately.